2023
DOI: 10.1017/s0266467423000184
|View full text |Cite
|
Sign up to set email alerts
|

Phenological diversity among sub-tropical moist forest trees of north-eastern India

Abstract: Analysing phenological diversity of tropical trees provides a potential tool to detect climate change effects and devise forest management options. In this study, the leaf phenological activity of 28 dominant tree species in a moist sub-tropical hill forest of north-eastern India was examined for a period of 2 years and related to functional traits (i.e. leaf mass per area (LMA) and wood density (WD)). The peak phase of leaf fall occurred in the cool dry period (November to January) with leaf flush peaking in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…So, the H value not only indicates the number of species but also shows us the abundance of the species distributions in the total number of species among the whole community. Hence, the diversity index value of this study falls within the range reported for tropical forests [48,68]. Species richness along the river basin is influenced by edaphic, biotic and climatic factors [69].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…So, the H value not only indicates the number of species but also shows us the abundance of the species distributions in the total number of species among the whole community. Hence, the diversity index value of this study falls within the range reported for tropical forests [48,68]. Species richness along the river basin is influenced by edaphic, biotic and climatic factors [69].…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, 105 species from mining sites in four districts of Khyber Pakhtunkhwa, Pakistan was reported by [46]. The overall sum of species included in the study was greater than the sum of species listed by other studies; including [47] recorded 92 species from a mid-elevation forest in the Central Himalayas of India, while [48] reported 123 species from a tropical forest in Manipur, north India. Similarly, 85 species from Dulahazara Garjan, Bangladesh by [49], and investigators in tropical forests in various regions of the globe, for example, 89 species were reported by [50], 52 species were recorded by [51], and 94 species was reported by [52].…”
Section: Discussionmentioning
confidence: 66%
“…Interannual rainfall variability -high rainfall years and drought years including cycles like the El Niño Southern Oscillation and the Indian Ocean Dipole -can result in interannual variability in tree phenophase onset and intensity (Medway 1972, Zimmerman et al 2007, Chang-Yang et al 2016, Chapman et al 2018, Dunham et al 2018, Pau et al 2018. There is a growing understanding of the influence of environmental factors on leaf phenology of tropical species, but information on reproductive phenology is lacking (Chaturvedi et al 2021, Devi et al 2023. To predict future phenological shifts in the tropics, an important first step is to understand the extent of environmental controls on tropical tree reproductive phenology.…”
Section: Introductionmentioning
confidence: 99%